Doing Business in Pakistan 2010 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Pakistan 2010 is the first country-specific subnational report of the Doing Business series in Pakistan. The report builds on the regional Doing Business in South Asia 2005-7 series, which created quantitative indicators on business regulations for 6 Pakistani cities. Doing Business in Pakistan 2010 documents progress in the previously measured cities and extends the analysis to a total of 13 cities. Comparisons with Karachi and the rest of the world are based on the indicators in Doing Business in 2010: reforming through difficult times, the seventh in a series of annual reports published by the World Bank and the International Finance Corporation. The indicators in Doing Business in Pakistan 2010 are also comparable with the data in other subnational Doing Business reports. Doing Business investigates the ways in which government regulations enhance or restrain business activity. The cities covered in Doing Business in Pakistan 2010 were selected jointly with Pakistan's Ministry of Finance and are the following: Faisalabad (Punjab), Gujranwala (Punjab), Hyderabad (Sindh), Islamabad (Islamabad Capital Territory, or ICT), Karachi (Sindh), Lahore (Punjab), Multan (Punjab), Peshawar (Khyber Pakhtunkhwa), Quetta (Balochistan), Rawalpindi (Punjab), Sheikhupura (Punjab), Sialkot (Punjab), and Sukkur (Sindh). Regulations affecting six stages of the life of a business are measured at the subnational level in Pakistan: starting a business, dealing with construction permits, registering property, enforcing contracts, trading across borders, and paying taxes. These indicators have been selected because they cover areas of local jurisdiction or practice. The data in Doing Business in Pakistan 2010 are current as of December 2009.